The Influence of Bullying on Positive Emotions and Their Effect as Mediators between Controllable Attributions of Success and Academic Performance - Antonio Ragusa; Valeria Caggiano; Ana Isabel Obregón-Cuesta; Jerónimo J. González-Bernal; Jessica Fernández-Solana; Luis Alberto Mínguez-Mínguez; Benito León-; Santiago Mendo-Lázaro; Ema Di Petrillo; Josefa González-Santos (MDPI AG, 2023)
Academic performance (AP) is a topic of particular interest in the academic context. Attributions for academic success (AAS) have been shown to have a significant impact on AP, and more specifically internal controllable attributions (ICA) are closely linked to academic success. Similarly, positive emotions (PE) have a significant influence on AP and may in turn be influenced by bullying. This study examines the connections between ICA of academic success and AP mediated through PE in late primary and early secondary school students and analyzes the relationships between PE and bullying categories. Students (N = 562, 49.46% female, Mage = 11.6 SD = 1.2) reported on their perceptions of ICA and PE in relation to exams and their relationship with bullying through validated questionnaires. The AP was obtained as the average mark of all subjects in the immediately preceding assessment. First, a multiple linear regression analysis considering ICA and PE as predictor variables was carried out, which showed a significantly positive link between ICA and PE, between ICA and AP, and between PE and AP. Subsequently, using the SPSS macro PROCESS, a simple mediation model was implemented to quantify the effect of ICA on AP through PE in exams, and finally an ANOVA between the categories of bullying and PE was performed. The results showed a significant indirect relationship with a positive predictive relationship for AP. The model shows that PE proves to be a significant mediator between ICA and AP, and it is shown that students disengaged from bullying score higher in PE.